The Impact of Increased Maternal sFlt-1/PlGF Ratio on Motor Outcome of Preterm Infants - Middendorf, Lisa; Gellhaus, Alexandra; Iannaccone, Antonella; Köninger, Angela; Dathe, Anne-Kathrin; Bendix, Ivo; Reisch, Beatrix; Felderhoff-Mueser, Ursula; Huening, Britta (Frontiers in Endocrinology, 2022)
Background The sFlt-1 (soluble fms-like tyrosine kinase-1)/PlGF (placental growth factor) ratio serves as a clinical biomarker to predict the hypertensive, placenta-derived pregnancy disorder pre-eclampsia which is often associated with placental dysfunction and fetal growth restriction. Additionally elevated levels also indicate an increased risk for prematurity. However, its predictive value for subsequent neonatal neurological outcome has not been studied. Objective This study aimed to evaluate the correlation of maternal sFlt-1/PlGF ratio with early motor outcome of preterm infants. Design/Methods: 88 preterm infants (gestational age ≤ 34 + 0) born between February 2017 and August 2020 at the Department of Obstetrics and Gynecology, University Hospital Essen in Germany, were included, when the following variables were available: maternal sFlt-1/PlGF levels at parturition and general movement assessment of the infant at the corrected age of 3 to 5 months. The infants were stratified into high and low ratio groups according to maternal sFlt-1/PlGF cut-off values of 85. To investigate the early motor repertoire and quality of spontaneous movements of the infant, the Motor Optimality Score (MOS-R) based on antigravity movements and posture patterns, was applied. In the given age, special attention was paid to the presence of fidgety movements. Linear regressions were run to test differences in infants motor repertoire according to the maternal sFlt-1/PIGF ratio. Results Linear regression analysis showed that the sFlt-1/PlGF ratio does not predict the MOS-R score (β=≤0.001; p=0.282). However, children with birth weight below the 10th percentile scored significantly lower (mean 20.7 vs 22.7; p=0.035). These children were 91% in the group with an increased ratio, which in turn is a known predictor of low birth weight (β= -0.315; p <0.001). In the group with a high sFlt-1/PLGF ratio above 85 the mothers of female infants had a lower average sFlt-1/PlGF ratio compared to a male infant (median: 438 in female vs. 603 in male infant, p=0.145). Conclusions In our cohort, especially low birth weight, which correlated with an elevated sFlt-1/PlGF ratio, had a negative effect on the outcome in the MOS-R. A direct correlation between an increased ratio and a worse motor outcome was not demonstrated.